RESTORASI LINGKUNGAN DALAM AL-QUR’AN PERSPEKTIF TAFSIR AL-MISHBĀH (PENDEKATAN TEORI ETIKA LINGKUNGAN) - dan Afifullah, Nurhayati Khairul Mutaqin (Program Studi Ilmu Al-Qur'an dan Tafsir, Universitas Islam Negeri Datokarama Palu, 2023)
Human needs are met by nature, such as food, clothing, and shelter. But the fact is that there is an imbalance between nature and humans; humans pay less attention to the preservation of nature, as evidenced by used baby diapers scattered on Badur Beach, Sumenep, and other beaches. The Qur'an provides solutions for environmental restoration efforts, the discussion of which is focused on the book Tafsir Al-Mishbāh. The method used is library research using the approach of environmental ethics theory. This article will discuss three problem formulations: 1) How does the Qur'an explain the issue of environmental restoration? 2) How are the Qur'anic verses about environmental restoration interpreted in Tafsir Al-Mishbāh? 3) How is the interpretation of the Qur'anic verses on environmental restoration in Tafsir Al-Mishbāh according to the theory of environmental ethics?. Gratitude as an issue of environmental restoration in the Qur'an, which is non-physical, can be realized by humans with an attitude of justice, honesty, and care. These three attitudes are equivalent to the theory of biocentrism, which considers all living things as the center, both human and non-human. Similarly, the theory of ecocentrism does not only focus on living things but also covers the surrounding natural conditions.